Memes como estrategia publicitaria: Caso Holcim - Ecuador - Arreaga Olavarria, Beatriz Agustina (2020)
Advertising combined with memes is the best way to advertise without having a rejection or users being overwhelmed by the advertisement, this new form is more successful than standard advertising because the meme itself has a level of being viral on platforms or social networks since the meme always refers to a recent event, mixing these two tools results in a timely and consumable advertising campaign In this present project, the meme will be analyzed as an advertising strategy in the Holcim-Ecuador case, through this research it will be possible to contribute more about this new way of carrying out digital advertising and it would be of great help if the students of the last semester of the Social Communication career of the Babahoyo Technical University have more information about this format, as it would help in their future careers as communicators.